The Effects of the Pd-TiN Seed Layer on the Magnetic Properties of Co/Pd Multilayered Media - Kim, SungMan; Chun, DongWon; Lee, JungJoong; Jeung, WonYoung (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
We investigated a Pd-TiN thin film as a seed layer for a [Co/Pd] multilayered perpendicular magnetic recording media. The 15-nm Pd-TiN thin film and [Co(0.2 nm)/Pd(0.8 nm)] multilayered media were fabricated by dc magnetron sputtering without heating the substrate. The Pd-TiN(20 vol.%) granular seed layer with apparent grain boundaries is considered to provide suitable seeds to [Co/Pd] multilayer and reduced the magnetic exchange coupling of [Co/Pd] grains causing an increase of the perpendicular coercive field and a decrease of the magnetic cluster size for the [Co/Pd] multilayered media. These results suggest that the Pd-TiN seed layer contributed to the formation of physically well-separated [Co/Pd] multilayered grains, improving the magnetic properties of [Co/Pd] multilayered media.
Keywords: RECORDING MEDIA; PERPENDICULAR MEDIA; COB/PD MULTILAYERS; UNDERLAYER; SEEDLAYER